1998
DOI: 10.1183/09031936.98.12030601
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leukocyte integrins and tissue factor in mononuclear phagocytes

Abstract: The development of adult respiratory distress syndrome (ARDS), infant respiratory distress syndrome (IRDS) and septicaemia is known to be associated with pulmonary intravascular, interstitial and intra-alveolar deposition of fibrin [1]. The formation of fibrin during injury and inflammatory reactions, followed by its clearance during the repair process, is the result of a dynamic interplay between coagulant and fibrinolytic factors which amongst other cells are synthesized by peripheral blood monocytes, lung a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The actual procoagulant expressed by a defined macrophage/monocyte population may vary dependent on the differentiation state of the cell and on the type of inflammatory stimulus employed. Although tissue factor is by far the best documented and most frequently studied monocyte/macrophage procoagulant (1,(8)(9)(10)(11)(12)(13)(14)(15), several other compo-nents of the coagulation cascade are known to be expressed by monocytes/macrophages. It has been shown that human lung macrophages display Factor VII-like activity and contain Factor VII mRNA (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The actual procoagulant expressed by a defined macrophage/monocyte population may vary dependent on the differentiation state of the cell and on the type of inflammatory stimulus employed. Although tissue factor is by far the best documented and most frequently studied monocyte/macrophage procoagulant (1,(8)(9)(10)(11)(12)(13)(14)(15), several other compo-nents of the coagulation cascade are known to be expressed by monocytes/macrophages. It has been shown that human lung macrophages display Factor VII-like activity and contain Factor VII mRNA (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages retrieved by bronchoalveolar lavage may not be representative of those that remain adherent to the alveolar epithelium. Such differences may be explainable by the known relationships between integrin expression, cell adherence, and macrophage phenotype (41).…”
mentioning
confidence: 99%